(untitled) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2022)
Rooting on mature stem cuttings of the Drumstick tree, Moringa oleifera, Lam. Moringaceae, was studied using three auxins (indole-3-acetic acid (IAA), indole-3-butyric acid (IBA) and maphthalene acetic acid (NAA) at two seasons. The experiments were carried out at random using a 342 factorial design. The growth of stem cuttings prior to rooting was influenced by auxin concentrations and the seasons. Stem cuttings taken during the wet season and treated with 500 mg/L of IBA, NAA, and IAA sprouted 18-27 days sooner than dry season cuttings (24-30 days after planting or DAP). Wet-season bud development into leaves was found to be more affected by auxin application and seasons than dry-season bud development (2.0%-83.4% wet season and 10%-56.08% dry season). The results also demonstrated that the stem cuttings did not callus, but instead formed nodules at the base of the stem regardless of the treatment or time of year. Sizes ranging from small (S) to medium (M) to large (B) nodules were spotted. Larger concentrations of auxins (500 mg/L of IBA, NAA, and IAA) influenced the production of smaller nodules during the dry season, while in the wet season, 500 mg/L of the three auxins influenced the production of larger nodules (B), and 300 mg/L of the auxins influenced the production of smaller nodules (M). Auxin concentration and control affected the production of small (S) nodules. The results also showed that large nodules were associated with the tap, lateral, and feeding roots. High auxin concentration (500 mg/L) affected these. The wet season stem cuttings produced more tap roots than the dry season cuttings. The study showed that vegetative propagation of M. oleifera by rooting stem cuttings is best done in the wet season. Wet season cuttings produced proto-type seedlings of the parent stock.